Simplification Study of FE Model for 1000kV AC Transmission Line Insulator String Voltage and Grading Ring Surface Electric Field Distribution Calculation - Guoli Wang; Zheng Zheng; Daochun Huang; Zhengfang Huang; Jiangjun Ruan; Yifan Liao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The finite element model of the 1000kV Ultra High Voltage (UHV) AC transmission line porcelain insulator string voltage distribution and grading ring surface electric field distribution calculation has the characteristics of large size, complicated structure and various mediums. To insure the accuracy, related influencing factors should be considered to simplify the model reasonably for improving computational efficiency. A whole model and a simplified 3D finite element model of UHV AC transmission line porcelain insulator string were built. The influencing factors including tower, phase conductors, hardware fittings, yoke plate and phase interaction were considered in the analysis. And finally, the rationality of the simplified model was validated. The results comparison show that building a simplified model of three-phase bundled conductors within a certain length, simplifying the tower reasonably, omitting the hardware fittings and yoke plate and containing only single-phase insulator string model is feasible. The simplified model could replace the whole model to analyze the voltage distribution along the porcelain insulator string and the electric field distribution on the grading ring surface, and it can reduce the calculation scale, improve optimization efficiency of insulators string and grading ring parameters. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3833